575 Washington Street, March 6, 1923 (Tufts Archival Research Center, 2005)
Street-level view northwest of 575 Washington Street, located between Avery Street to the west-southwest and West Street to the east-northeast. Signage adorns the facade of the building, which faces east-southeast. Commercial products are displayed in the storefront windows, and a man is visible along the left side of the photograph. 7 15/16 x 9 15/16 Photographs